The Tipping Point : how little things can make a big difference - Gladwell, Malcolm (New York: Back Bay Books Little Brown, 2001)
Tipping Point is that magic moment when an idea, trend, or social behaviour crosses a threshold, tips, and spreads like wildfire. The book brilliantly illuminates the tipping point phenomenon, is already changing the way people throughout the world think about selling products and disseminating ideas.
Includes index
uaj 30/7/2013, ijb 17/04/2019
Loans
Keywords: Social Psychology; Contagion (Social psychology); Causation; Context effects (Psychology)